2006
DOI: 10.1073/pnas.0506618103
|View full text |Cite
|
Sign up to set email alerts
|

The activity of a human endoplasmic reticulum-associated degradation E3, gp78, requires its Cue domain, RING finger, and an E2-binding site

Abstract: Efficient targeting of proteins for degradation from the secretory pathway is essential to homeostasis. This occurs through endoplasmic reticulum (ER)-associated degradation (ERAD). In this study, we establish that a human ubiquitin ligase (E3), gp78, and a specific E2, Ube2g2, are both critically important for ERAD of multiple substrates. gp78 exhibits a complex domain structure that, in addition to the RING finger, includes a ubiquitin-binding Cue domain and a specific binding site for Ube2g2. Disruption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
224
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(232 citation statements)
references
References 40 publications
8
224
0
Order By: Relevance
“…Coexpression of wild-type gp78-Myc had no effect on the degradation of CFTR⌬F508-GFP (Supplemental Figure 3), even though it enhanced the ubiquitylation of CFTR⌬F508-GFP. Overexpression of gp78 has been shown to accelerate the degradation of other gp78 substrates Song et al, 2005;Chen et al, 2006), which suggests that additional factor(s) are required for the degradation of CFTR⌬F508. HEK293 cells transiently expressing CFTR⌬F508-GFP and HA-ubiquitin, with or without (control lane) the indicated ubiquitin ligases, were lysed and subjected to immunoprecipitation by using anti-GFP antibody, followed by immunoblot using anti-HA antibody.…”
Section: Gp78 Is Involved In Erad Of Cftr⌬f508mentioning
confidence: 99%
See 2 more Smart Citations
“…Coexpression of wild-type gp78-Myc had no effect on the degradation of CFTR⌬F508-GFP (Supplemental Figure 3), even though it enhanced the ubiquitylation of CFTR⌬F508-GFP. Overexpression of gp78 has been shown to accelerate the degradation of other gp78 substrates Song et al, 2005;Chen et al, 2006), which suggests that additional factor(s) are required for the degradation of CFTR⌬F508. HEK293 cells transiently expressing CFTR⌬F508-GFP and HA-ubiquitin, with or without (control lane) the indicated ubiquitin ligases, were lysed and subjected to immunoprecipitation by using anti-GFP antibody, followed by immunoblot using anti-HA antibody.…”
Section: Gp78 Is Involved In Erad Of Cftr⌬f508mentioning
confidence: 99%
“…The association of gp78 with CFTR⌬F508 was mediated by its intrinsic CUE domain, which also has ubiquitin binding activity (Supplemental Figure 4; Zhong et al, 2004;Chen et al, 2006). To determine whether the ubiquitin binding region of the CUE domain overlapped the CFTR⌬F508 binding region, we generated a gp78 mutant in which the ubiquitin binding site in the CUE domain, MFP (amino acids 463-465), was mutated to AAR.…”
Section: The Cue Domain Of Gp78 Is Required For Cftr⌬f508 Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…RING finger E3s usually interact with cognate E2s via the RING domain. However, gp78 was reported to contain a second E2 binding site named G2BR (24). To understand how gp78 interacts with Ube2g2 to assemble a functional E3-E2 heterooligomer, we determined the crystal structure of Ube2g2 bound to a 28-residue peptide corresponding to the G2BR domain of gp78.…”
Section: Structure Of Ube2g2mentioning
confidence: 99%
“…We also showed that gp78 forms an oligomer that might be critical for E2 active site-associated polyubiquitination (16). gp78 is a multispanning membrane protein anchored to the ER membrane with its catalytic domain facing the cytosol (23,24). To identify the domains responsible for gp78 oligomerization, we expressed Flag-tagged, full-length gp78 (Flaggp78) together with GFP-fusion proteins comprising either the N-terminal transmembrane segments (gp78N-GFP) or the Cterminal cytosolic domain (gp78C-GFP) of gp78 in cells.…”
mentioning
confidence: 99%